In Vitro Skin Models and Their Predictability in Defining Normal and Disease Biology, Pharmacology, and Toxicity. (June 2016) - Danilenko, Dimitry M.; Phillips, Gail D. Lewis; Diaz, Dolores
In vitro skin model systems are increasingly being used both in the early evaluation of therapeutic drug candidates and in confirmatory mechanistic studies. The most commonly used of these in vitro model systems are reconstituted human epidermis (RHE) models. These RHE models consist solely of epidermal keratinocytes, which comes with some limitations but also with the advantage of focusing toxicologic and pharmacologic evaluation on keratinocytes alone. RHE models can generally be implemented more quickly, easily, and reproducibly than in vivo models and can thus be used for high throughput compound screening while potentially reducing the need for animal studies. Histologic evaluation of RHE sections can be done quite easily, and the sections are very amenable to quantification via image analysis, including automated analysis. RHE model systems can provide very valuable early indications of therapeutic candidate biology, pharmacology, and toxicity; and early results have demonstrated that RHE models have been quite predictive for in vivo pharmacologic and toxicologic effects on the skin, including clinical skin toxicity.